Ripper : a novel - Allende, Isabel; Brock, Oliver (Translator); Wynne, Frank (New York : Harper, 2014)
"A fast-paced mystery involving a brilliant teenage sleuth who must unmask a serial killer in San Francisco through Ripper, the online mystery game she plays with her beloved grandfather and friends around the world"--
Originally published in Spain in 2014 by Random House Mondadori.
Keywords: Teenagers -- Fiction; Serial murderers -- California -- San Francisco -- Fiction; Internet games -- Fiction; FICTION / Thrillers; FICTION / Suspense; FICTION / Crime; Mystery fiction; Suspense fiction